The influence of workplace on overall health in Slovenia and Lebanon – empirical research - Maamari, Bassem E. (2015)
The article presents the influence of business premises’ factors of the workplace on satisfaction with the workplace and their impact on the state of health and health care of employees. The research compares respondents’ answers of Lebanon and Slovenia. The purpose of the research is to discover the influence and to facilitate the improvement of employee health through the application of base parameters and consequently the changes of workspace and work processes.